Integration between Indonesian Sharia Stock Index and Türkiye Sharia Index Using the Generalized Autoregressive Conditional Heteroscedasticity Model - Rahayu, Siti; Sawitri, Peni; Ülev, Salih; Fathiyakan (AL-MUZARA'AH, 2024)
Indonesia and Türkiye are countries with a large number of followers of Islam. These two countries have a lot of cooperation in various activities. This study aims to measure the integration between Islamic capital markets in Indonesia and Türkiye. For the Indonesian Islamic capital market index, the Indonesian Islamic Stock Index (ISSI) is used, while for Türkiye, the Borsa Katilim (KATLM) is used. Using the Generalised Autoregressive Conditional Heteroscedasticity (GARCH) method, it was found that during the observation year, although there was a lot of cooperation, the activities of these two countries were not integrated. This can provide ideas for further research related to why there is a lot of cooperation between countries but it does not result in integration.